Pengaruh Kompensasi, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Pegawai dengan Budaya Organisasi sebagai Variabel Intervening pada Non PNS di Kantor Wilayah Dispora Pasaman Barat - Arzu Khairani; Hilda Mary; Desi Permata Sari (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research aims to find out big facts. Discussion of the influence of compensation, work discipline and work motivation on employee performance with organizational culture as an intervening variable for non-civil servants at the West Pasaman Dispora Regional Office. The data analysis method is in the form of questionnaire data with a sample of 60 respondents. The data analysis method used is questionnaire data analysis. The research results obtained based on the partial test (T test) were obtained: There is no influence of Compensation on Organizational Culture for West Pasaman Dispora Consumers, There is an influence of Work Discipline on Organizational Culture for West Pasaman Dispora Consumers, There is no influence of Work Motivation on Organizational Culture for West Pasaman Dispora Consumers, There is no influence of Compensation on Employee Performance for Dispora Consumers West Pasaman., There is an influence of Work Discipline on Employee Performance among West Pasaman Dispora Consumers. There is an influence of Work Motivation on Employee Performance among West Pasaman Dispora Consumers. This indicates that the better the work motivation felt by West Pasaman Dispora consumers, the higher their employee performance. There is no influence of organizational culture on employee performance among West Pasaman Dispora consumers. Organizational culture is unable to influence compensation variables on performance. Employees, Organizational Culture Not able to influence the Work Discipline variable on Employee Performance, Organizational Culture Not able to influence the Work Motivation variable on Employee Performance. Finally, the author suggests to companies the need for company management to pay special attention to improving employee performance through the variables that have been studied.